Analisis Debit Air Limpasan Di Permukaan (Run Off) Pada Das Batang Kandih Dan Das Air Dingin Sebagai Penyebab Terjadinya Genangan Di Kota Padang - Hero Willy Ikhsan Ordheo; Rusli HAR (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract.The Purpose of this study is to calculate rainwater discharge into the groundthrough the infiltration process and water discharge that become a inundation on thesurface, when it rains highest in on the DAS Batang Kandih and DAS Air Dingin. DAS AirDingin has an infiltration rate of around 0,10852 cm/minutes and the value of infiltration inthe DAS Air Dingin is 65.402,5331 m3/hour/km2 with catchment area 20.844 km2 and soilcatchment area on the DAS Air Dingin very low with time around 0,1 to 0,2 per minutes.Meanwhile infiltration rate on the DAS Batang Kandih is 0,128 cm/minutes and the value ofinfiltration in the study area is 76.775,58 m3/hour/km2. Form the result of this study theinfiltration value in this area as very small because it enters the VI/E zone. Calculation ofaverage daily maximum rainfall using Polygon Thiessen Method is 163,359 mm/day with areturn period of 25 years of rainfall is 277,005 mm/day. Rain intensity at DAS Air Dingin is32,760 hours and rain intensity at DAS batang Kandih is 32,935 hours. calculation of runoff discharge value at DAS Air Dingin is 811,370 m3/seconds and calculation of run offdischarge value at DAS Batang Kandih is 863,188 m3/seconds.Keywords:infiltration, rainfall, rainfall return period, rain intensity, run off